2021
DOI: 10.1109/access.2021.3110604
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge-Based Clinical Decision Support System Utilizing an Intelligent Ensemble Voting Scheme for Improved Cardiovascular Disease Prediction

Abstract: A massive amount of medical data is available in healthcare industry, which can be utilized to extract useful knowledge. A Clinical Decision Support System (CDSS) is used to improve patient"s safety by minimizing medical errors. Heart disease is one of the major chronic maladies even in todays" world. Many researchers have employed different data mining techniques to predict heart disease. The objective of proposed framework is to improve the accuracy of heart disease prediction. In this paper, an ensemble bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Further, NB optimized with grid search found to provide accuracy of 84.8%. Instead of conventional model, an ensemble based majority voting scheme is proposed by researchers [18]. Outliers in the dataset are identified and removed using filter based techniques.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Further, NB optimized with grid search found to provide accuracy of 84.8%. Instead of conventional model, an ensemble based majority voting scheme is proposed by researchers [18]. Outliers in the dataset are identified and removed using filter based techniques.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Additionally, a novel voting strategy based on ensemble learning was proposed in [25], which made use of six ML algorithms: NB, SVM, DT, neural network (NN), MLP, and single-layer perceptron. The researchers found that, on average, the ensemble model achieved 83% accuracy, which was higher than any of the individual methods.…”
Section: Related Workmentioning
confidence: 99%
“…Heart disease is considered a chronic disease that can be detected earlier by measuring various health standards, e.g., blood pressure, cholesterol, heart rate, and glucose level [2]. Heart disease does not affect human health alone; it affects the capabilities of countries and their economies [3]. That is, heart disease is a serious disease in which the rate of occurrence is very high, especially in developing countries, due to the lack of knowledge of its symptoms [4].…”
Section: Introductionmentioning
confidence: 99%